A fauna de Braconidae (Hymenoptera: Ichneumonoidea) na região de Campos do Jordão, São Paulo, Brasil - Gomes, Silvana Angélica Gama (Universidade Federal de São Carlos, 2005)
This work had as main objective to carry through a study of the Braconidae (Hymenoptera) fauna in Campos do Jordão, SP, using Malaise traps and "sweeping" at the vegetation in 15 points in different altitudes (600 to 2000 m). About 3580 specimens, distributed in 23 subfamilies, 103 genera and 1420 morphospecies have been collected during the four collects carried through two dry seasons and two rain seasons, from November, 2001 to September, 2002. We have obtained climate data and vegetation data, in each point, to characterize and to relate them with the frequency of occurrence, richness and diversity of the Braconidae fauna. The greatest density and diversity have occurred during the rain season and the most abundant groups, in both seasons, were the Microgastrinae, Helconinae, Doryctinae and Alysiinae. Statistical analyses have indicated that the frequency of occurrence of some Braconidae groups was influenced by the different altitude. The greatest Braconidae diversity occurred at the1500 m of altitude and the greatest equitability at the 1300 m, demonstrating the preference for points with opened areas, where the luminosity is high, and contribute to the development of the vegetation, that is the food source to its hosts. The asymptote phase of the genera richness was not reached in none of the sampled points. The flight species phenology of the 23 subfamilies was also studied. The more commom subfamilies were the coinobiont Microgastrinae and the idiobiont Doryctinae. All the collected parasitoids have presented two peaks of occurrence at the same time, November/December (2001) and September/October (2002). The females were more commom than the males and they presented their peaks of ocurrence at same time. The coinobionts and idiobionts species had presented an increase in the abundance during the periods when the temperature and the rainfall had been higher. A new Doryctinae genus, a new Heterospathius and Helconichia species were described and illustrated. The Campos do Jordão region is favorable to the development and maintenance of the Braconidae fauna and therefore its preservation must be considered.
Keywords: Ecologia; Himenóptero; Braconidae; Mata Atlântica; Altitude; CIENCIAS BIOLOGICAS::ZOOLOGIA